Analisis Dampak Pendanaan Konstruksi Proyek Pembangunan PrasaranaLight Rail Transit Jabodebek (Studi Kasus: PT Adhi Karya (Persero) Tbk.) - Permata, Ki Syahgolang (Kajian Ekonomi dan Bisnis, 2018)
Based on Presidential Decree no. 98 Year 2015 and its amendments, PT Adhi Karya (Persero) Tbk. was assigned to build the Jabodebek LRT which includes: lanes (including elevated construction), stations, and operating facilities. The purposes of this study are to understand the analysis of project’s funding evaluation, to find the best funding scheme which options consist of Availibility Payment, Deferred Payment and Corporate Financing through Government Capital Injection (PMN) and to understand the impact of these funding schemes toward ADHI’s performance. Based on the analysis of existing data, it can be concluded by using Availability Payment and Deferred Payment schemes there will be significant increases in debt interest compared to Corporate Financing through PMN. Therefore, the best financing alternative is Corporate Finance through PMN.